2020
DOI: 10.1099/jmm.0.001162
|View full text |Cite
|
Sign up to set email alerts
|

Myoviridae phage PDX kills enteroaggregative Escherichia coli without human microbiome dysbiosis

Abstract: Introduction Bacteriophage therapy can be developed to target emerging diarrhoeal pathogens, but doing so in the absence of microbiome disruption, which occurs with antibiotic treatment, has not been established. Aim Identify a therapeutic bacteriophage that kills diarrhoeagenic enteroaggregative Escherichia coli (EAEC) while leaving the human microbiome intact. Methodology Phages from wastewater in Portland… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 65 publications
0
29
1
Order By: Relevance
“…The overuse and misuse of antibiotics in the treatment of diarrhea have led to an alarming increase of AMR in diarrheagenic bacteria [ 1 , 2 , 3 ]. Phage therapy has been effective at reducing E. coli burden in the murine gut with antibiotic pretreatment [ 5 , 6 , 7 , 8 ]. Although C. rodentium is widely used as an exemplary in vivo model system for gastrointestinal bacterial diseases [ 9 , 86 ], there are no reports using this species for phage therapy development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overuse and misuse of antibiotics in the treatment of diarrhea have led to an alarming increase of AMR in diarrheagenic bacteria [ 1 , 2 , 3 ]. Phage therapy has been effective at reducing E. coli burden in the murine gut with antibiotic pretreatment [ 5 , 6 , 7 , 8 ]. Although C. rodentium is widely used as an exemplary in vivo model system for gastrointestinal bacterial diseases [ 9 , 86 ], there are no reports using this species for phage therapy development.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse models for the study of EPEC diseases have had limited utility, because gastrointestinal microbiota defends well against human E. coli infections [ 4 ]. Consequently, most mouse models of E. coli gastrointestinal diseases require substantial antibiotic pre-treatment to reduce resident bacteria [ 5 , 6 , 7 , 8 ]. The preferred surrogate for EPEC diseases is the mouse-restricted pathogen Citrobacter rodentium [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to consider phages as a key component of the microbiome in further analysis of FMT [ 38 ]. A recent study has shown that phageome alone may be sufficient to eliminate C. difficile infection and restore a healthy microbial structure [ 39 ]. The evaluation was performed in five patients with symptomatic CD with chronic relapse.…”
Section: Role Of Phages In Gastrointestinal Diseases and Their Potmentioning
confidence: 99%
“…In all cases, FFT restored normal stool habits and removed C. difficile symptoms for at least 6 months. These results highlight that bacteriophages alone modulate the bacterial community restoring homeostasis [ 39 ].…”
Section: Role Of Phages In Gastrointestinal Diseases and Their Potmentioning
confidence: 99%
See 1 more Smart Citation